Design and Optimization of Ladder Wave Digital Filters - Abdul Samad, Salina (Malaysian Journal of Computer Science, 1997)
This paper introduces a time domain approach for designing ladder wave digital filters (WDFs) with limited coefficient wordlengths. Simple iteration equations yield the time domain response of a ladder WDF. An optimization algorithm then facilitates the design of the WDF to meet a desired response with a specific number of bits representing the coefficients. This approach also affords realizations with frequency domain constraints.